ANALISIS EFEKTIVITAS MEDIA KONKRET DAN MEDIA DIGITAL WORDWALL DALAM MEMBANGUN PEMAHAMAN MATEMATIKA SISWA DI SEKOLAH DASAR - Awliya, Aliyah Isti'anah; Putri, Hafiziani Eka; Subiyanto, Callista; Septiani, Dian Nazilla; Perangin-Angin, Jethro Joshua; Siregar, Sabarina Zahara (STKIP Persada Khatulistiwa Sintang, 2026)
Mathematics learning in elementary schools still faces various challenges due to the abstract nature of the material, which is not always aligned with students’ concrete operational stage of cognitive development. Therefore, innovative learning media are needed to facilitate conceptual understanding and enhance learning motivation. One such innovation is the use of concrete media and digital media such as Wordwall. This study aimed to analyze the effectiveness of concrete media and Wordwall as a digital learning tool. The research employed a literature review method by collecting, analyzing, and synthesizing findings from previous relevant studies. The results indicate that concrete media improve learning mastery by allowing students to directly observe and manipulate objects, making mathematical concepts easier to understand. Meanwhile, Wordwall is effective in reinforcing practice and increasing student engagement through interactive activities, with some studies reporting participation rates exceeding 80%. The use of both media benefits teachers by providing varied instructional strategies, facilitating content delivery, and enhancing assessment effectiveness. However, challenges include limited facilities, technological readiness, and teachers’ competence in integrating media effectively. In conclusion, the integration of concrete media and Wordwall is considered effective in creating engaging, meaningful, and 21st-century-relevant mathematics learning.